Q02 A randomised, double-blind, placebo-controlled phase IB pharmacodynamic study with selisistat (SEN0014196) in HD patients. (29th August 2012) - Süssmuth, SD; Landwehrmeyer, GB; Tabrizi, SJ; Andersen, C; DiBacco, M; Tripepi, G; Westerberg, G; ,
Abstract : Background: Siena Biotech SpA is developing selisistat (SEN0014196) as a potentially disease-modifying therapy for HD. Selsistat is a potent and selective SirT1 inhibitor (IC50 98 nM) that has shown benefit across a range of preclinical models for HD, from cells and neurons transfected with mutant huntingtin to transgenic Drosophila and R6/2 mice. The compound has shown to be safe and well tolerated in healthy volunteers and has a favourable pharmacokinetic profile. Aim: The current study was designed to provide biophase samples for analysis of a series of potential target engagement and disease-modification read-outs, helping to establish a proof-of-principle and aid in dose selection for future safety and efficacy studies. Methods: A total of 63 HD patients with a wide range of CAG repeats and disease burden scores were screened across six sites in Germany (Bochum, Ulm), Poland (Krakow, Warsaw) and the UK (London, Manchester). Patients were randomised to receive either 10 or 100 mg of selisistat or placebo for 2 weeks. Safety data collected included vital signs, ECGs, clinical laboratory parameters and type and frequency of adverse events. Clinical assessments included UHDRS and a cognitive battery. Serial blood sampling for pharmacokinetics and pharmacodynamics was performed on days 1 and 14 and at follow-up after a washout phase of 14 days. Results and Conclusions: A total of 55 patients completed the treatment as per protocol; there were four screening failures and four patients withdrew consent. No Serious Adverse Events were reported and no patient withdrew from the study as a result of an adverse event. We will present full data on safety, tolerability, pharmacokinetics and clinical assessments, while pharmacodynamic data will be reported elsewhere.